Biological control of tick populations: review and reflections - Labarthe Norma V. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1994)
This study is concerned with aspects of the relationship between ticks and their hosts that have a bearing on biological control of tick populations. It proposes control methods based on a program that would combine development of an effective vaccine with genetic selection of hosts.